Fertility of sheep and goats in Slovenia - Drobnič, Marjana; Kompan, Drago; Komprej, Andrija (Acta Agraria Kaposváriensis, 1999)
Trait and parameter definitions for the evaluation of fertility in sheep and goats in Slovenia are discussed. Fertility results for sheep and goats in controlled Slovenian herds for the period 1995–1999 are presented. The average litter size in 1998 was 1.45 (born)/1.36 (live) in sheep, and 1.73 (born)/1.67 (live) in goats. The number of lambs born per ewe per year was 1.97 in sheep and 1.7 in goats.
Keywords: sheep; goats; fertility; lamb production; performance recording